A novel model for testing the efficiency of removal of calcium hydroxide from complex root canal anatomies. (13th January 2017) - Küçükkaya Eren, Selen; Aksel, Hacer; Parashos, Peter
Abstract: The purpose of this study was to evaluate the efficacy of several irrigation protocols in the removal of calcium hydroxide [Ca(OH)2 ] from simulated internal root resorption cavities in a complex root canal anatomy model. The 20° to 35° curved mesiobuccal roots of 94 maxillary molars were sectioned longitudinally; internal resorption cavities were prepared in the apical third of the canal walls. Calcium hydroxide was placed into the cavities and the root halves reassembled. Four teeth were used as controls, and 90 teeth were randomly divided into six experimental groups ( n = 15), according to the irrigation protocols used: syringe irrigation; H2 O2 (HP); Navitip FX; Vibringe‐syringe; Vibringe‐NaviTip FX; ultrasonically activated irrigation (UAI) using an ultrasonic K‐file. In the HP group, 2.5% NaOCl and 3% H2 O2 were used, while 2.5% NaOCl and 17% EDTA were used in the remaining groups. Stereomicroscope images and radiographs were used to measure the remaining Ca(OH)2 . The model proved to be suitable for simulating complex anatomy. Positive correlation was found between stereomicroscope and radiographic analyses ( P < 0.05). UAI removed significantly more Ca(OH)2 than the other experimental groups ( P < 0.05). The HP group was the least efficient protocol ( P < 0.05). It would appear that a reliable model has been developed that simulates complex root canal anatomy. Irrigant activation protocols enhanced Ca(OH)2 removal.